Investigating Plasticity Differences in the Motor Area in Tourette’s Syndrome, using Non-Invasive Brain Stimulation - Salvage, Jennifer R. A. (2023)
Tourette’s syndrome (TS) is a neurodevelopmental disorder characterised by motor and phonic tics, which have been linked to over excitability in the motor areas within the brain. The primary aim of this thesis was to investigate those with a diagnosis of TS and explore the use of non-invasive brain stimulation techniques in these relevant motor areas. It is hypothesised that those with this developmental condition may have an altered pattern of plasticity in the brain areas related to motor movements, making this a key target in TS research using transcranial magnetic stimulation (TMS). TMS is a widely used non-invasive brain stimulation technique that can be used to investigate and modulate cortical excitability. In doing so, it can provide interesting insights about brain plasticity.